Prevalence of HIV, Hepatitis B, and C in a Public Hospital in Mexico - Diego-Ponce, Guillermo; Baldovinos-Leyva, Irma (Revista Acciones Médicas, 2024)
Blood donation in public hospitals may present certain risks related to infections such as Hepatitis B (HBV), C (HCV), and the Human Immunodeficiency Virus (HIV), which constitute a public health issue and, consequently, a critical factor in transfusion medicine. A retrospective descriptive methodology was employed to ensure that every individual evaluated as a blood donor at the ISSSTE Hospital could be screened for the potential prevalence of HBV, HCV, and HIV. Out of 6,841 selected cases, 19.14% were women, and 80.86% were men, with a prevalence of 0.29 for HIV, 0.11 for HBV, and 0.29 for HCV. The study concluded that this is likely because the population donating blood is generally healthy, and most donors are relatives of patients scheduled for surgery at the same hospital.